(untitled) (Annals of the University of Bucharest. Political Science Series, 2025)
This article aims to present a comprehensive analysis of study-related migration of Moldovan ethnics from the Transnistrian region, also known as a post-Soviet unrecognized entity. The Transnistrian region is a narrow strip of land located between Ukraine and the Republic of Moldova, which is affected by massive migration flows. The young people of the Transnistrian region are inclined to migrate permanently to neighbouring countries and Western EU member states. Nevertheless, the phenomenon of migration from the disputed land is an under-researched topic. Therefore, this study aims to determine the particularities of this phenomenon, the main root causes and the perception of students concerning studies abroad, life in a disputed territory, and the impact of the unresolved status issue. The research is based on a two-pronged approach in order to determine the complexity and the magnitude of study-related migration. It presents the results of 20 semi-structured interviews conducted with students who graduated from Moldovan-administered Latin-script schools and it analyses the data provided by Transnistrian and Moldovan institutions. A special attention is given to graduates of Romanian language schools because their decision to migrate is influenced by a more diverse combination of push and pull factors.